Re-engineering Modern Marketing for Organizational Growth in South Africa Post COVID - Naidoo, Audrey (Global journal of Business and Integral Security, 2024)
This research study empirically investigates the re-engineering modern marketing for organizational growth in South Africa post-COVID. The pandemic has necessitated both the need for new theoretical value creation in marketing discipline, together with the practical application within the broader business context. The pandemic served as a tipping point for both organizations and modern marketing, fostering a tenfold alteration that opens up an excellent window of opportunity for the reconfiguration of modern marketing. The research design for this study is qualitative research approach, conducting semi-structured interviews with 19 experienced marketing participants, based on real world experiences of the interviewees, leading to new discoveries and contextual theoretical findings. The findings highlight the need for marketers to adapt to the nuances of a globalized world, learning from global experiences and utilizing global capabilities. The challenges faced by modern-day marketers, such as the undefined role of marketing, the dichotomy of experiences in bureaucratic environments, the struggle to demonstrate viii relevance and ROI, and the fragmentation of data sets. These results highlight the need for marketers to advance and adopt a strategic approach, data-savvy, and flexible in order to promote organizational success. Modern marketing has revolutionized the purpose of marketing within organizations, expanding its spheres of impact beyond traditional marketing functions. The emphasis on the customer experience, which is at the center of the redesign of modern marketing, is what spurs this change. All of the empirical data on design-led operating models, such as agile operating models, hybrid-operating models, and the emergence of marketing as a service design, are contained in the findings. This gave rise to the idea of a human centric approach, which introduces a fundamental change in the function of marketing within organizations. This suggests an entirely novel conceptual framework for modern marketing emphasizing the value of empathy, trust and authentic connections. The significance of this study if three-fold: the theoretical adaption of modern marketing that can adapt to its ever-changing environment, secondly the practical application of this study on how modern marketing should organize themselves to lead the growth agenda and finally the contribution of this study to the field of marketing is multi-faceted and substantive.